2018
DOI: 10.1042/bcj20180470
|View full text |Cite
|
Sign up to set email alerts
|

Identification of active site residues implies a two-step catalytic mechanism for acyl-ACP thioesterase

Abstract: In plants and bacteria that use a Type II fatty acid synthase, isozymes of acyl-acyl carrier protein (ACP) thioesterase (TE) hydrolyze the thioester bond of acyl-ACPs, terminating the process of fatty acid biosynthesis. These TEs are therefore critical in determining the fatty acid profiles produced by these organisms. Past characterizations of a limited number of plant-sourced acyl-ACP TEs have suggested a thiol-based, papain-like catalytic mechanism, involving a triad of Cys, His, and Asn residues. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…However, the well-known and widely used approach of analyzing fatty acid components produced by thioesterases heterologously expressed in E. coli provided an efficient and fast way to study the in vivo activity of these enzymes. In this experimental system, we were not able to observe 3-ketoacids directly but rather assumed their presence on the basis of the detection of 2-methylketones following chemical decarboxylation of the 3-ketoacids [9,30]. GmMKS2-X2, for which the corresponding cDNA was isolated from the immature seeds of G. max, produced primarily 2-tridecenone (13:1) and smaller amounts of other odd-chain methylketones (7:0, 9:0, 11:0, 11:1, 13:0, 15:0, 15:1, and 17:1) when expressed in E. coli and upon heat-activated decarboxylation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the well-known and widely used approach of analyzing fatty acid components produced by thioesterases heterologously expressed in E. coli provided an efficient and fast way to study the in vivo activity of these enzymes. In this experimental system, we were not able to observe 3-ketoacids directly but rather assumed their presence on the basis of the detection of 2-methylketones following chemical decarboxylation of the 3-ketoacids [9,30]. GmMKS2-X2, for which the corresponding cDNA was isolated from the immature seeds of G. max, produced primarily 2-tridecenone (13:1) and smaller amounts of other odd-chain methylketones (7:0, 9:0, 11:0, 11:1, 13:0, 15:0, 15:1, and 17:1) when expressed in E. coli and upon heat-activated decarboxylation.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of the predicted Cys active site residue to Ala resulted in approximately 70% reduced activity compared to wild-type, thus it is possible that this Cys residue is important for substrate binding J o u r n a l P r e -p r o o f Journal Pre-proof but not catalytic activity, or that mutation of this residue perturbs the function of the conserved adjacent Glu 319 . Furthermore, multiple sequence alignment of 1019 acyl-ACP TE sequences collected from the ThYme database revealed that Cys 320 is only conserved among 22% of the 1019 sequences, and appears restricted to plant acyl-ACP TEs [144].…”
Section: Te14 Familymentioning
confidence: 99%
“…Binding of the substrate positions the thioester bond adjacent to the catalytic network. Two similar mechanisms have been proposed based on the structures of TE14 thioesterases, and while they differ in the exact role of the catalytic residues, in general, both mechanisms involve a nucleophile that attacks the thioester carbonyl carbon to form an acyl-anhydride intermediate, which is subsequently hydrolysed by water molecules to release non-esterified fatty acids [141,144].…”
Section: Te14 Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Limited structural information and a not well-understood catalytic mechanism for acyl-ACP TEs 26,27 makes it challenging to increase the activity of this enzyme by rational design. Directed evolution, which mimics the natural evolutionary process at the lab scale, is a promising alternative approach, and provides a mechanism to identify and exploit genetic space that natural evolution may not have explored [28][29][30] .…”
Section: Introductionmentioning
confidence: 99%